FENOMENA SOSIAL IBU RUMAH TANGGA PEMAKAI JASA BANK KELILING DI DESA SUKOANYAR KECAMATAN WAJAK KABUPATEN MALANG - Kholisotul Bariroh; Rizki Agung Novarianto (IKIP Budi Utomo Malang, 2023)
Abstract: A mobile bank is where customers don't have to go to the bank to deposit money, they can even borrow money from a mobile bank without having to worry about complicated conditions. This study aims to determine the social phenomenon of housewives who use mobile bank services in the village of Sukoanyar. This research uses a type of qualitative method with a descriptive approach. The method of collecting data in this study is using observation, interviews and documentation. The results found in this study are that it is known that the social phenomenon of mobile banking by the way it works is very helpful to the community in terms of the process of applying for loans that are fast, easy, and there is no guarantee. But the people's economy is getting worse, because of high interest rates. There are two impacts felt by the community after borrowing from mobile banks. It turns out that there are more negative impacts than positive impacts. The conclusion of this study is that in terms of the loan application process which is fast, simple, and does not require collateral, the community greatly benefits from the existence of mobile banks in the way they operate. However, high interest rates are a downturn in the people's economy. In terms of income, the standard of living of traders has not been increased by mobile banks. Keywords: Mobile Bank, qualitative, observation, interview